The Effect of Promotions, Discounts and Service Quality In Repurchasing Interest In Grabfood Application - Irawan, Stami; Albari , Albari (Green Publisher Indonesia, 2023)
This research aims to explain and analyze the effect of promotions, discounts on repurchase intention through service quality to Grabfood customers in Indonesia. This research used simple random sampling. The research objects were women and men aged at least 18 years who accessed Grabfood and had made purchases at Grabfood. There were 250 samples. Data collection was carried out by distributing questionnaires electronically. The research variables were promotions and discounts as the independent variables, service quality as the mediation variable and repurchase intention as the dependent variable. This research used AMOS 24.0 to analyze the data. The results of the research showed that Promotion had significant and positive effect on Service Quality, Discount did not have significant effect on Service Quality, Service Quality had positive and significant effect on Repurchase Intention, Promotion had significant and positive effect on Repurchase Intention, and Discount did not have significant effect on Repurchase Intention